Big things from small beginnings: Creating and scaling community-based opportunities for sustainable small and local businesses - Yang, Man; Ehrnström-Fuentes, Maria; Wincent, Joakim (Journal of Business Venturing, 2025)
How can communities be active to create and scale opportunities for sustainable small and local businesses? We address this question through a longitudinal study of a community-based initiative, which promoted sustainability in food production and consumption and has scaled to different communities worldwide. To improve our understanding of the entrepreneurial role of communities, we observed how communities proactively engaged in processes evolving from replicating and developing community ventures to scaling community movement over time. Through these processes, we identified three mechanisms— infrastructure shift , nurturing , and sustaining infrastructure . Our research extends current theories of community-based entrepreneurship by offering a process perspective at the community level and elaborating how communities collectively create and scale opportunities for sustainable small and local businesses, allowing an idea to evolve from a small initiative to a large movement.